O pensamento indígena: o xamanismo ameríndio como terapia da mente - Correia, Wandreus Wilson da Silva (2021)
This dissertation aims to discuss shamanism while thought, way of life and immanent "virtuality"; in this way, to verify the indigenous sociability with its own environment, and what kind of production happens with the encounter of multiplicity of bodies in a cosmos of fluid transversality. The idea is also to occasionally oppose the western “neurotized” environment, its “agencies”, and the anthropocentric culture. The path to explore different categories, concepts, lexicons, and elements of a two-way anthropology, will be covered mainly through the work of the anthropologist Eduardo Viveiros de Castro (1986; 2006; 2007; 2009; 2014) in dialogue with the “philosophy of difference” by Deleuze & Guattari (2011; 2012), punctuated with the theoretical framework of Sciences of Religions. The outcome seeks to develop a post-structuralist articulation, which allows a thought construction analysis through "afecção", "affections", relationships, making possible the perception of a possible mind therapy in the "spirituality and health" line.